Modeling of 137Cs Dispersion in the Atlantic Ocean at Ahanta West Coast: A Hypothetical Candidate Site for Ghana’s First Nuclear Power Plant - Aggrey, Y. A.; Amo-Boateng, M.; Kpeglo, D. O.; Muslim, M.; Prasteyo, A. T. (National Research and Innovation Agency, 2024)
The government of Ghana has the intention of adding nuclear to its energy mix. Due to water availability for cooling, the coastal areas will be the right place for siting a nuclear power plant. This study was carried out to assess the distribution of 137Cs should liquid radioactive waste be released into coastal waters because of a non-routine event. The distribution was studied for the first month after the release. In the first week following the release, 137Cs was distributed within 16 km of the Ahanta West coastal waters with a concentration of about 9.1 Bq. L-1. On the seventh day, the distribution reached the entire coast of the Nzema East with a lower concentration with the bulk of the concentration still in the Ahanta waters. The 137Cs continued to spread into the eastern coast until the thirty-first day with a concentration of less than 1 Bq. L-1. This study provides useful data for future monitoring along the coast.